2012
DOI: 10.3324/haematol.2011.061408
|View full text |Cite
|
Sign up to set email alerts
|

Anti-CD20 IgA can protect mice against lymphoma development: evaluation of the direct impact of IgA and cytotoxic effector recruitment on CD20 target cells

Abstract: The online version of this article has a Supplementary Appendix. BackgroundWhile most antibody-based therapies use IgG because of their well-known biological properties, some functional limitations of these antibodies call for the development of derivatives with other therapeutic functions. Although less abundant than IgG in serum, IgA is the most abundantly produced Ig class in humans. Besides the specific targeting of its dimeric form to mucosal areas, IgA was shown to recruit polymorphonuclear neutrophils a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
33
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 50 publications
3
33
0
Order By: Relevance
“…However, in vitro studies documented that myeloid effector cells-and PMN in particular-were more effective in ADCC by IgA than by IgG1 antibodies (11)(12)(13). Human IgA antibodies demonstrated significant antitumor activity in huFcaRI-transgenic mice, which are required to investigate Fc-mediated effector functions of this antibody isotype in vivo, because mice do not express a functional FcaRI orthologue (30,44,45). However, the serum halflife of recombinant human IgA antibodies in mice was unexpectedly short-probably due to rapid clearance by the ASGPR (30,31) and the lack of binding to FcRn.…”
Section: Antibody Isotypes For Tumor Immunotherapymentioning
confidence: 99%
“…However, in vitro studies documented that myeloid effector cells-and PMN in particular-were more effective in ADCC by IgA than by IgG1 antibodies (11)(12)(13). Human IgA antibodies demonstrated significant antitumor activity in huFcaRI-transgenic mice, which are required to investigate Fc-mediated effector functions of this antibody isotype in vivo, because mice do not express a functional FcaRI orthologue (30,44,45). However, the serum halflife of recombinant human IgA antibodies in mice was unexpectedly short-probably due to rapid clearance by the ASGPR (30,31) and the lack of binding to FcRn.…”
Section: Antibody Isotypes For Tumor Immunotherapymentioning
confidence: 99%
“…Bispecific antibodies simultaneously targeting CD20 and the myeloid receptor for IgA (FcαRI; CD89) demonstrated that polymorphonuclear cells (PMN) could effectively kill lymphoma cells by targeting CD20 (Stockmeyer et al , ). Subsequently, a CD20 antibody of human IgA isotype demonstrated in vitro and in vivo efficacy against lymphoma cells, but the mode of action of this antibody has not been fully characterised (Pascal et al , ). IgA antibodies constitute an important part of the mucosal immune system and differ from IgG in structure and function.…”
mentioning
confidence: 99%
“…Bispecific antibodies simultaneously targeting CD20 and the myeloid receptor for IgA (FcaRI; CD89) demonstrated that polymorphonuclear cells (PMN) could effectively kill lymphoma cells by targeting CD20 (Stockmeyer et al, 2000). Subsequently, a CD20 antibody of human IgA isotype demonstrated in vitro and in vivo efficacy against lymphoma cells, but the mode of action of this antibody has not been fully characterised (Pascal et al, 2012). IgA antibodies constitute an important part of the mucosal immune system and differ from IgG in structure and function.…”
mentioning
confidence: 99%